(untitled) (Південний архів (історичні науки), 2025)
ON THE WAY TO YOURSELF. REVIEW OF THE BOOK OF TURCHENKO F. G. FROM THE CHALLENGES OF THE ERA. MEMOIRS OF A HISTORIAN. ZAPORIZHZHYA: PUBLISHING HOUSE "HELVETICA", 2023. 400 P.